Cutting stems before relaxing xylem tension induces artefacts in Vitis coignetiae, as evidenced by magnetic resonance imaging. (19th October 2015) - Ogasa, Mayumi Y.; Utsumi, Yasuhiro; Miki, Naoko H.; Yazaki, Kenichi; Fukuda, Kenji
Abstract: It was recently reported that cutting artefacts occur in some species when branches under tension are cut, even under water. We used non‐destructive magnetic resonance imaging (MRI) to investigate the change in xylem water distribution at the cellular level in Vitis coignetiae standing stems before and after relaxing tension. Less than 3% of vessels were cavitated when stems under tension were cut under water at a position shorter than the maximum vessel length (MVL) from the MRI point, in three of four plants. The vessel contents remained at their original status, and cutting artefact vessel cavitation declined to <1% when stems were cut at a position farther than the MVL from the MRI point. Water infiltration into the originally cavitated vessels after cutting the stem, i.e. vessel refilling, was found in <1% of vessels independent of cutting position on three of nine plants. The results indicate that both vessel cavitation and refilling occur in xylem tissue under tension following stem cutting, but its frequency is quite small, and artefacts can be minimized altogether if the distance between the monitoring position and the cutting point is longer than the MVL.